The development of play-based physical training to improve physical fitness of the soccer players in the 10-12 years age group - Florentius Ferri Persada Panorama; Sugiyanto Sugiyanto; Muchsin Doewes (Kazimierz Wielki University, 2018)
The background of the research is the needs of physical training design which is suitable with the characteristics of the soccer school players in the 10-12 years age group in Yogyakarta. Based on this problem, this study aims to improve the physical fitness of the soccer school players in the 10-12 years age group in Yogyakarta by applying the play-based physical training design. The research method used in this study is the "developmental research method (Research and Development)" proposed by Borg and Gall. The researcher adapted the research procedures into three main stages: 1. needs analysis, 2. product's development and product's testing, and 3. product's effectiveness testing. The first stage is a needs analysis which was conducted by interviewing the soccer coaches. It is found out that the most applied physical training design is the conventional one and is unfortunately less effective for the children because it does not go in accordance to the their age's characteristics. The second stage is developing the product by means of the experts' testing and evaluation resulting in 88,19% and is ready for the next product's testing. The small group test result came in 83,28%, while the bigger group test resulted in 87,25%. The third stage is product's effectiveness testing by comparing the groups given the play-based physical training design and the conventional one using the pre-test and post-test research designs. The range obtained from the physical fitness pre-test and post-test as follows: (1) body composition: experiment group of 0,12 and controlled group of 0,17, (2) strength: experiment group of 4,53 and controlled group of 3,17, (3) muscle endurance: experiment group of 2,53 and controlled group of 1,53, (4) flexibility: experiment group of 0,83 and controlled group of 0,4, (5) cardio respiratory endurance: experiment group of 1,61 and controlled group of 1,2. To conclude, the play-based physical training design significantly improves the physical fitness of the soccer school player in the 10-12 years age group in Yogyakarta. It is quite important to note that the final product of play-based physical training design comes in the form of a guidebook.